A Concise Protocol for the Validation of Language ENvironment Analysis (LENA) Conversational Turn Counts in Vietnamese. (February 2018) - Ganek, Hillary V.; Eriks-Brophy, Alice
The aim of this study was to present a protocol for the validation of the Language ENvironment Analysis (LENA) System's conversational turn count (CTC) for Vietnamese speakers. Ten families of children aged between 22 and 42 months, recruited near Ho Chi Minh City, participated in this project. Each child wore the LENA audio recorder for a full day. Two native speakers listened to 10-min extracts of the recordings from each family and labeled conversational turns according to the coding protocol. Their results were compared with the findings from the LENA software. A Spearman rank correlation test indicated a strong level of correlation between the LENA software and the human coders, r s (18) = .70, p < .001. The LENA System's CTC provides a reasonably accurate estimate of conversational turns in Vietnamese recordings, showing that this protocol can yield significant results. Discrepancies between the coders and the software are discussed, and the strengths and weaknesses of the proposed protocol are highlighted.